2021
DOI: 10.1111/ipd.12891
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychosocial determinants of adverse childhood experiences and severe early childhood caries among First Nations children

Abstract: Adverse childhood experiences (ACE) can have substantial repercussions for a child's overall health, and although ACE research on oral health is not extensive, findings do support a link between ACE and children's oral health status. 1 In a 2008 Canadian study using data from the Children's Aid Society of Toronto, researchers found that early childhood caries (ECC) was not only more prevalent in children who were maltreated, but also more severe, with a nearly 9-fold difference in mean decayed teeth (dt) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…Except four journal articles (one duplicate report of the same study, 39 one with the same data source, 38 and two with insufficient required data 36,40 ), the other six reports were all considered for meta‐analysis. Two studies independently reported outcomes for each study subgroup; therefore, they were separately incorporated into the systematic review and meta‐analysis 13,15 . Of these, only the data from one subgroup were dependent (two different outcomes from one single population) 13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except four journal articles (one duplicate report of the same study, 39 one with the same data source, 38 and two with insufficient required data 36,40 ), the other six reports were all considered for meta‐analysis. Two studies independently reported outcomes for each study subgroup; therefore, they were separately incorporated into the systematic review and meta‐analysis 13,15 . Of these, only the data from one subgroup were dependent (two different outcomes from one single population) 13 .…”
Section: Resultsmentioning
confidence: 99%
“…This condition may lead to some serious health, developmental, and social consequences through changing children's dietary intakes 10 . Several cross‐sectional studies have also suggested the association between FI and childhood dental caries, albeit with some inconsistencies 12–15 . Moreover, with the ongoing battle with COVID‐19, there have been increases in FI, affecting vulnerable households globally 16 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Socio-economic factors such as caregiver education, household financial hardship, household overcrowding, parents' occupation and employment status have been reported to affect the capacity of Australian Indigenous children to afford private dental services. 28 The Australian Government has implemented strategies to curb financial barriers such as the Child Dental Benefits Schedule (CDBS) which provides utilisation/number of children without reduced dental service utilisation. CI, confidence interval; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The socio‐economic disadvantage of the Australian Indigenous population can limit access to dental services, which exacerbates the development and implications of dental caries 24 . Socio‐economic factors such as caregiver education, household financial hardship, household overcrowding, parents' occupation and employment status have been reported to affect the capacity of Australian Indigenous children to afford private dental services 28 . The Australian Government has implemented strategies to curb financial barriers such as the Child Dental Benefits Schedule (CDBS) which provides benefits for dental services, and the Dental Relocation and Infrastructure Scheme (DRISS), which provides relocation and infrastructure support grants for dental providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation